Learning from the wisdom of practice: teachers' educational purposes as pathways to supporting adolescent purpose in secondary classrooms. Issue 5 (19th October 2016) - Quinn, Brandy P.
Abstract: Purpose in life is beneficial for adolescents and their communities. However, less is known about supports for purpose development during adolescence, particularly in the school setting. The study described here drew from theories about teacher beliefs and knowledge, and a multidimensional definition of purpose in life, in order to learn from practising teachers about the ways in which supporting adolescent purpose may fit within their existing beliefs about their work with students. The specific aims were to explore alignment between teachers' educational purposes and their own definitions of purpose in life with the 'personal meaning' and 'beyond-the-self' dimensions of purpose in life. Nine secondary school teachers from the United States who taught in a variety of academic content areas were interviewed using a semi-structured protocol. Transcripts were coded according to two dimensions of purpose: personal meaning and beyond-the-self consequences. Teacher responses revealed alignment between their educational purposes and the dimensions of 'personal meaning' and 'beyond-the-self consequences'. At the same time, teacher definitions of the unified construct of purpose in life did not reflect this same integration of the dimensions of purpose. Implications for teacher education and future research are discussed.